Global warming and German agriculture: Impact estimations using a restricted profit function - Günter Lang (Universität Augsburg, Institut für Volkswirtschaftslehre, 1999)
This study uses the concept of shadow prices for measuring the impacts of climate change. Estimation of a restricted profit function rather than a cost or a production function increases the explanatory power of the agroclimate approach because of an endogenous output structure. Using micro-based panel data on Western German farmers, the results im-ply that the agricul-tural production process is significantly influenced by climate conditions. By linking this model with a climate-change scenario, a remarkable positive shadow value is found for the German agricultural sector. Interestingly, the spatial distribution of the gains shows no concentration on those regions, which currently suffer from insufficient temperature. Finally, the importance of an endogenous output structure is confirmed by the finding that the de-sired product mix will drastically change.
urn:nbn:de:bvb:384-opus4-276674
Keywords: Q12; Q25; 330; Climate change; impact study; agriculture; restricted profit function